Measuring Dynamics of Infant-Adult Synchrony Through Mocap - Cuadros, Zamara; Hurtado, Esteban; Cornejo, Carlos (Frontiers in Psychology, 2019)
The temporal dynamics of parent-infant synchrony have been well documented. In recent years, the introduction of more accurate technologies for tracking movements has allowed the distinction of different morphological patterns of dyadic coordination. However, the potential of these technologies to explore infant-adult synchrony has not yet been explored. In the present study, we examined the temporal, spatial, and morphological synchrony patterns of infant-unknown adult pairs participating in a storytime session by a motion capture system (mocap). We find low but significant correlation levels of body synchrony between infants and unknown adults. This synchronized coactivity adopted two differentiated forms: mirror-like and anatomical. While the infants' movements mirrored those of the adults with a lag [0.9 s], the adults' reactions to the infants were anatomical with delay [0.4 s]. This evidence could contribute novel insights to rethink synchrony and its measurement.